2008
DOI: 10.1353/eas.0.0004
|View full text |Cite
|
Sign up to set email alerts
|

Matching Extension Service with Farmers' Needs: Towards Combining Social and Agro-Ecological Approaches in Ethiopian Extension

Abstract: An extension service grounded in the social, economic and ecological realities of the farming family and the farm can better target its programs to meet farmers' needs. In this study 305 farm households, from two districts of north-central Ethiopia are used as a case study, to examine key socio-economic and ecological indicators that affect effective use of extension services. Data was collected using the household questionnaire method and analysed using univariate statistical methods to see factors that impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The 35% of the male farmers in grade 5 to 8 is, even, specifically true only for that area in the country. Berhanu (2008), for instance, in a study conducted in North-Central part of Ethiopia indicated much lower numbers of farmers who reach to grade level educational status. Therefore, a high level of illiteracy among farming communities, and particularly in female farmers is a characteristic feature in Ethiopia.…”
Section: Educational Statusmentioning
confidence: 97%
“…The 35% of the male farmers in grade 5 to 8 is, even, specifically true only for that area in the country. Berhanu (2008), for instance, in a study conducted in North-Central part of Ethiopia indicated much lower numbers of farmers who reach to grade level educational status. Therefore, a high level of illiteracy among farming communities, and particularly in female farmers is a characteristic feature in Ethiopia.…”
Section: Educational Statusmentioning
confidence: 97%
“…Despite the large number of livestock population in the country, the output from the sub-sector is low and the rate of growth has been poor, lagging far behind the population growth rates (Brokken et al, 1991). In the same passion, the income from the sector is very minimal as compared to the potential of the live animal population in the country and commercial transformation will lead to enhanced income and livelihood changes (Berhanu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%